Monitoring Land Use and Land Cover Using Remote Sensing Technology in Kubu Raya Regency, West Kalimantan Province - Nur Rahmadhanti, Intan; Salsabila Nur'Aini; Herni Natasha Aulia; Muhammad Ikhwan Ramadhan; Hanum Resti Saputri; Abd Malik A Madinu; Ali Dzulfigar; Rahmat Asy'Ari; Rahmat Pramulya; Yudi Setiawan (Faculty of Agriculture, Tompotika Luwuk University, 2024)
Kubu Raya Regency is one of the areas that has a peat ecosystem in it. The peat ecosystem has a role and function in mitigating climate change because it has the ability to store quite high carbon reserves. However, peat ecosystems often experience degradation and changes in land cover which can contribute carbon emissions to the atmosphere. Remote sensing is a technology that can be used to detect changes in land cover and use in Kubu Raya Regency. Therefore, this research aims to detect changes in land cover and using remote sensing technology and assess the level of accuracy of the detection results. Analysis of changes in land cover and use from 2000 - 2023 was obtained by guided classification using the Random Forest (RF) algorithm which involves various vegetation, water and built-up land indices. The research results show that there is a decrease in forest land area from 2000 to 2023 amounting to 106,542 ha. The forest area in 2000 was 524,359 ha, while in 2023 it will be 417,817 ha. The results of accuracy measurements show an overall accuracy (OA) value of 98.84% with a kappa statistic of 0.98. It is hoped that the results of these findings will provide an initial picture of the condition of the ecosystem in Kubu Raya Regency, most of which is a peat ecosystem, as a consideration in formulating peat ecosystem conservation policies.